Validitas dan Praktikalitas Modul Laju Reaksi Terintegrasi Eksperimen dan Keterampilan Proses Sains untuk Pembelajaran Kimia di SMA - Andromeda, Andromeda; Ellizar, Ellizar; Iryani, Iryani; Bayharti, Bayharti; Yulmasari, Yofita (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
Modules are one of the learning materials that can be used in the learning process. Modules compiled based on guided inquiry learning syntax and integrating experimental activities that will be able to improve students science process skills. This study aimed to produce a reaction rate module based on guided inquiry integrated experiments and valid student science process skills and practical use in senior high school  chemistry learning. The type of this research was research and development (R & D) and the development model used was the 4-D model which consists of four stages: (1) define, (2) design, (3) development, (4) desseminate. This research was limited to the validity and practicality test. The validity test was carried out by 5 experts and limited trials to reveal the practicality done at SMAN 1 Lubuk Basung. The research instrument used was in the form of a validity and practicality questionnaire which was analyzed using kappa moment (k) Data analysis showed that the average moment of kappa validity was 0.84 with a very high validity category. The average practical kappa moments from teachers and students were respectively 0.83 and 0.85 with a very high practicality category. These results were also supported by the analysis of students answers in answering critical questions, exercises, prelab questions, postlab questions, and worksheets in modules, with an average value of 90.2. Based on the results of the study it can be concluded that the guided inquiry integrates experiments and science process skills on based reaction rate topic are valid and practical used for chemistry learning in senior high school.